Do Organic Inputs in African Subsistence Agriculture Raise Productivity? Evidence from Plot Data of Malawi Household Surveys - Wouter Zant (Tinbergen Institute, 2014)
We exploit plot data from the agricultural module of the third Malawi Integrated Household Survey (IHS-3) to investigate how organic cultivation techniques contribute to productivity of non-subsidized local maize and what to expect from using organic inputs on a larger scale. We approximate organic inputs with crop combinations and livestock, and use matching techniques for estimating impacts. Productivity of local maizebean, local maizegroundnut and local maizenkhwana, each combined with livestock and chemical fertilizer, is shown to be statistically similar to productivity of fertilized maize mono-cropping. Simulations show that large increases in total maize production are potentially feasible under conversion to organic cultivation techniques. Limited availability of labour and livestock are likely constraints.
Keywords: Q12; O13; O55; 330; crop productivity; soil fertility; organic inputs; Green Revolution; Malawi; Africa